Parametric Study of a Taut Compliant Mooring System for a FOWT Compared to a Catenary Mooring - Magnus Thorsen Bach-Gansmo; Stian Kielland Garvik; Jonas Bjerg Thomsen; Morten Thøtt Andersen (Journal of Marine Science and Engineering, 2020)
The catenary mooring system is a well recognized station keeping method. However, there could be economical and environmental benefits of reducing the footprint. In the last decades, more focus has been given to synthetic mooring lines and different mooring layouts to optimize the levelized cost of energy (LCOE) for offshore renevable energy converters such as wave energy converters. Therefore, this work presents a parametric study of two important parameters, namely the mooring line angle and line pretension, for a taut mooring configuration focusing on the dynamic response when applied to the TetraSpar floating foundation compared to a catenary mooring system. The work is based on experimental results conducted in the wave basin at Aalborg University (AAU) and compared to analytical stiffness calculations. In addition, a numerical model was tuned based on the main dynamics to achieve the tension response. The results showed satisfying dynamic behavior where the angle and pretension mainly influenced the surge and yaw natural periods. The motion response showed similar behavior between the chosen parameters, and larger pitch amplitudes were found compared to the catenary system.